Antibacterial Effects of Ascophyllum Nodosum and Punica Granatum Extracts on Streptococcus Mutans and Lactobacillus Acidophilus: Effects of extracts on oral bacteria - Ladan Moghaddam, Mahsa; Fattahi, Bafrin; aref, parissa; Tavasoli, Sara; Etemadi, Fathemeh; Motevaseli, Elahe (Journal of Dental School, 2025)
Objective(s): This research investigated the influence of Ascophyllum nodosum (A. nodosum) and Punica granatum (P. granatum) extracts on Streptococcus mutans (S. mutans) and Lactobacillus acidophilus (L. acidophilus). Methods: In this laboratory-based study, the antibacterial effects of aqueous-acidic, ethanolic, and methanolic extracts of A. nodosum, along with the hydroalcoholic extract of P. granatum were analyzed against S. mutans and L. acidophilus using the disc diffusion method. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the extracts were determined through broth microdilution and macrodilution techniques. As a positive control, 0.2% chlorhexidine (CHX) was utilized, and all experiments were performed in triplicate. Statistical analyses included ANOVA, the Bonferroni test, and Kruskal-Wallis at p<0.05. Results: CHX exhibited the highest inhibitory and bactericidal effects on both bacterial strains. While both extracts showed antibacterial potential against both organisms, their efficacy was significantly lower than that of CHX (P<0.05). The following CHX, aqueous acidic extract of A. nodosum and the hydroalcoholic extract of P. granatum demonstrated superior MIC and bacteriostatic activity against S. mutans. For L. acidophilus, the hydroalcoholic extract of P. granatum showed the best results. Conclusion: The results indicated that extracts from A. nodosum and P. granatum possess considerable antibacterial properties against S. mutans and L. acidophilus.